El aprestamiento escolar en el desarrollo de conocimientos de la prelectura del segundo año de Educación General Básica del "Cecib" (Centro Educativo Comunitario Intercultural Bilingüe) "Arturo Yumbay Ilijama" de la comunidad de Tingopamba, de la parroquia Guanujo, cantón Guaranda, provincia Bolívar, durante el año lectivo 2010 - 2011 - Tualombo Tenelema, Marlene Ederita (2012)
When concluding the present grade work it has been necessary to present in summarized form. The whole content of this copy in synthetic that next is detailed with the purpose of making know our social actors in a panoramic way the scientific content, the results and the proposal of the document. The formless present is the result of an investigation that was required of time, economy and of human talents with who he/she went possible to carry out the realization of this investigative work of grade. To undertake with this task it was necessary to present a project to the competent authorities whose topic was chosen previous to an analysis of the community reality that that more it was believed as a new topic with having deepened mainly by the previous investigations of momentous importance for the childhood and the community which we mention next. The chapter IV lastly are presented some proposals thoroughly with their essential parts to the third specific objective and this it consists on a series of methodologies and activities to carry out in the future for that which has been organized in operative square. It is also necessary to attach annexes and bibliographies of present work to facilitate the understanding to our kind readers and with pleasure we will receive the case recommendations and we accept errors that it is presented in this first edition of our topic. The chapter I. in those that it represents to the theoretical mark has taken out of books, pamphlets, internet to develop on the school aprestamiento as the understood scientific theory the outline of the main theories of prelectura knowledge. It is also enlarged these parts with the reduction, textual, contextual and the authors' person in what refers to the content of the variables. The second part denominated Conceptual Theory understands the consulted conceptual definition of other authors and expert in the famous authors. As they could not lack the descriptions, its historical review of the community where has been carried out investigations is presented as theory referencial. In the chapter II. It has been condemned the methodologies that we have used, since the inductive and deductive methods the investigation he/she has been carried out in a particular way in a school with the purpose of applying these results to improve the quality of the learning in the school aprestamiento to arrive to the prelectura. In the Chapter III. In this report it required the analysis of results it has been developed by means of encounters, squares graphic and statistical questionnaires to organize the tabulation based on what has been demonstrated that the hypothesis has outlined the conclusive part were guessed right where can see the results of this work and as being able to solve the problems presented results in the conclusions and the recommendations.